Conversion from external fixator to intramedullary nail causes a second hit and impairs fracture healing in a severe trauma model1. Issue 3 (15th October 2012) - Recknagel, Stefan; Bindl, Ronny; Wehner, Tim; Göckelmann, Melanie; Wehrle, Esther; Gebhard, Florian; Huber‐Lang, Markus; Claes, Lutz; Ignatius, Anita
Abstract In poly‐traumatic patients, second hits are known to potentiate the posttraumatic systemic inflammatory response, thus increasing the risk of multi‐organ dysfunction. In accordance with "damage control orthopaedic surgery" principles, fractures are initially treated with external fixators, which are replaced by internal osteosynthesis once the immunological status of the patient is considered stable. Recently, we demonstrated that a severe trauma impaired the healing of fractures stabilized by external fixation during the entire healing period. The question arose, whether switching to intramedullary nailing increases the inflammatory response in terms of a second hit, leading to a further impairment of bone healing. Wistar rats received a femoral osteotomy stabilized by an external fixator. Simultaneously half of the rats underwent an additional thoracic trauma. After 4 days, the external fixator was replaced by an intramedullary nail in half of the rats of the two groups. The inflammatory response was evaluated by measuring serum C5a levels. Fracture healing was determined by three‐point‐bending, µCT, and histomorphometry. The thoracic trauma significantly increased C5a concentrations 6, 24, and 72 h after the second surgical intervention. After 40 days, conversion to intramedullary nailing considerably decreased the flexural rigidity of the callus, with no significant differences between rats with or without thoracic trauma. After 47 days, flexural rigidity in rats subjected to conversion remained decreased compared to animals solely treated by external fixation, particularly in combination with blunt chest trauma. The results indicate that accumulation of second hits after multiple injuries could lead to aggravation of the fracture healing outcome. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 465–471, 2013